EXPERIENCES OF ACCESS TO DOCUMENTS IN ARCHIVES - KONTRIMAVIČIENĖ, DANUTĖ (Knygotyra, 2012)
Knowing the possibilities of access to records allows to better grasp the conception of access to records itself and its development for many centuries. As early as in the 4th c. B.C., in Athens, it was possible to familiarize with documents preserved at a repository. Later on, such a practice was forgotten for centuries, and only at the end of the 18th c. A.D. access to records was enforced. In the 19th–20th centuries, archives opened their doors and started sharing the accumulated information with the public. The beginning of the 21st c. has inherited not only the technological challenges, but also the practice of access of the second half of the 20th c., which in many countries is regulated by the archival legislation. The article deals with the development of access to records and the practice of access in the last decades. Various traditions and practices in different countries, as well as their legal systems provide different conditions of access to records preserved at repositories; it is important to know them in order to study records in a certain country. In the second half of the 20th c. the terms of access have been liberalized; they remain unchanged also in the 21st c., only the number of the countries that have established an open access to records or an open access after the records have been transferred to archives differs. However, in some countries, there remain restrictions of access to records, reaching 30 or even 70 years.
Keywords: ...